The Information-Content Of Earnings In A Discretionary Reporting Environment - Evidence From Nyse Industrials, 1905-10 (Vol 31, Pg 79, 1993) - Sivakumar, Kumar; Waymire, Gregory B. (Journal of Accounting Research, 1995)
Erratum